Vergleichende Untersuchungen über die Atmungsintensität der Zygopteren-Larven, zugleich ein experimenteller Beitrag zur funktionellen Bedeutung ihrer Analblätter (Odonata). - Münchberg, Paul (Contributions to Entomology = Beiträge zur Entomologie, 1962)
By means of respiratory activity measurements in different Zygoptera larvae the importance of the caudal lamellae as respiratory organs was justified. The whole respiratory surface of the investigated Zygoptera nymphs is divided among the caudal lamellae (20-35%) and the remaining body surface (65-80%). From a comparison between respiratory activity and body weight it is evident, that the respiratory efficiency of Anisoptera larvae, which are dependent on rectal respiration and do not strikingly move, is distinctly surpassed by Zygoptera nymphs. The method for determination of oxygen in water proposed by Winkler and Ohle is suitable for respiratory investihations, especieally as modified the by author.